Diversity and Morphological Characterization of Basidiomycota Macrofungi in Suco Manusae, Ermera Municipality - Luis da Costa; Antero F Branco; Celina Maria Godinho; Elisabet Andrijani Tarwanti; Monica S Martins (Immortalis Journal of Interdisciplinary Studies, 2026)
Macrofungi are an important group of fungi that play a key role in ecosystem processes, particularly in organic matter decomposition and nutrient cycling. This study aimed to identify macrofungal species and describe their morphological characteristics in Suco Manusae, Hatulia A Administrative Post, Ermera Municipality, Timor-Leste. An exploratory field survey was conducted during June 2025 using direct observation and specimen collection. Morphological identification was performed based on macroscopic features, including pileus shape and color, lamellae or pore structures, stipe characteristics, and substrate type. A total of 15 macrofungal species belonging to 9 families were recorded in the study area. Most species were found growing on decaying wood, while others were associated with soil and animal feces substrates. The results indicate that substrate availability and environmental conditions, particularly humidity and temperature, are important factors influencing macrofungal distribution and occurrence. This study provides baseline information on macrofungal diversity in Suco Manusae and contributes to the understanding of fungal ecological roles in tropical forest ecosystems. The findings may support future biodiversity monitoring and conservation strategies in the region.